PENERAPAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION DALAM UPAYA MENINGKATKAN KEMAMPUAN SISWA DI INDONESIA - Agus Putra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose in writing this work is the Application of the Student Team Achievement Division Learning Model in Efforts to Improve Students' Capability in Indonesia. This study analyzes the cooperative type learning model, namely the Student Team Achievement Division. This Student Team Achievement Division type learning model has succeeded in helping students learn well and develop their abilities in the classroom. The research method in this work is explanatory research. Step by step carried out while still paying attention to the rules of good writing. The steps taken by the author in carrying out the research are 1). The author conducts a background search of the problem, 2). The author searches related library sources, 3). The author conducts scientific arguments that still prioritize logic and 4). The author provides an explanation of the scientific answers found. The result of this work is that the cooperative learning model of the Student Team Achievement Division type is able to help improve students' ability to apply a good learning process. Teachers are expected to be able to develop cooperative type learning models well so that they can be carried out well too. The Student Team Achievement Division learning model is able to develop student motivation and enthusiasm in learning.